In Situ LID and Regeneration of PERC Solar Cells from Different Positions of a B-Doped Cz-Si Ingot. (4th January 2022) - Yuan, Shuai; Ding, Siqi; Ai, Bin; Chen, Daming; Jin, Jingsheng; Ye, Jiaxing; Qiu, Depeng; Sun, Xiaopu; Liang, Xueqin
Abstract : In order to investigate the light-induced-degradation (LID) and regeneration of industrial PERC solar cells made from different positions of silicon wafers in a silicon ingot, five groups of silicon wafers were cut from a commercial solar-grade boron-doped Czochralski silicon (Cz-Si) ingot from top to bottom with a certain distance and made into PERC solar cells by using the standard industrial process after measuring lifetimes of minority carriers and concentrations of boron, oxygen, carbon, and transition metal impurities. Then, the changes of their I -V characteristic parameters (efficiency η, open-circuit voltage V oc, short-circuit current I sc, and fill factor FF ) with time were in situ measured by using a solar cell I -V tester during the 1st LID (45°C, 1 sun, 12 h), regeneration (100°C, 1 sun, 24 h), and 2nd LID (45°C, 1 sun, 12 h). The results show that the LID and regeneration of the PERC solar cells are caused by the transition of B-O defects playing a dominant role together with the dissociation of Fe-B pairs playing a secondary role. The decay of η during the 1st LID is caused by the degradation of V oc, I sc, and FF, while the increase of η during the regeneration is mainly contributed by V oc and FF, and the decay of η during the 2nd LID is mainly induced by the degradation of I sc . After regeneration, the decay rate of η reduces from 4.43%–5.56% (relative) during the 1st LID to 0.33%–1.75% (relative) during the 2nd LID.